A risk score assessment tool for peripheral arterial disease in women: From the National Health and Nutrition Examination Survey. Issue 8 (17th August 2018) - Mansoor, Hend; Elgendy, Islam Y.; Williams, Renessa S.; Joseph, Verlin W.; Hong, Young‐Rock; Mainous, Arch G.
Abstract : Background: Peripheral arterial disease (PAD) carries a significant morbidity and mortality. Women are more commonly affected with this condition and are mostly asymptomatic, and undertreated. The objective of the study was to develop and validate a simple risk score to identify women with PAD. Hypothesis: Identifying those at early stage of the disease could help reduce the risk of complications. Methods: Using data from the National Health and Nutrition Examination Survey 1999‐2004, we identified women who had data on ankle brachial index. The cohort was divided into development (70%) and validation (30%) groups. Using variables that are self‐reported or measured without laboratory data, we developed a multivariable logistic regression to predict PAD, which was evaluated in the validation cohort. Results: A total of 150.6 million women were included. A diagnosis of PAD was reported in 13.7%. Age, body mass index, hypertension, diabetes mellitus, smoking, non‐oral contraceptive pill usage, and parity were all independently associated with PAD. The C‐statistics was 0.74, with good calibration. The model showed good stability in the validation cohort (C‐statistics 0.73). Conclusion: This parsimonious risk model is a valid tool for risk prediction of PAD in women, and could be easily applied in routine clinical practice.